THE OPTICAL COHERENCE TOMOGRAPHY (OCT) IN A PATIENT WITH RETINOPATHY-ASSOCIATED ECLAMPSIA: WHAT TO EXPECT? Poster Presentation - Case Report - General practitioner - Zain, Nurul Attikah; Sopha, Kasihana Hismanita (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eclampsia is a common pregnancy complication, that has been associated with retinopathy. Screening of retinopathy in preeclampsia/eclampsia is essential for early detection and management. Various imaging modalities are used to diagnose retinopathy. However, because of the higher-resolution imaging demand, optical coherence tomography (OCT) suggests a better option. The present study aimed to report the OCT findings of retinopathy-associated eclampsia. Case Illustration : A 24-year-old pregnant woman in 27th-week gestation with eclampsia presented the new onset of bilateral sudden diminution of vision. The vision in her right eye was limited to hand movement and that in her left eye was light perception only. Clinical examination revealed Siegrist streaks, Elschnig spots, and flame shape hemorrhages. OCT of both eyes demonstrated subretinal fluid, intraretinal fluid, thickening of the retinal layer, also inner retinal hyperreflectivity. Two months after the follow-up, there was an improvement in the OCT findings and also in the visual acuity. Discussion : An increase in macular thickness could be a characteristic feature in the OCT of retinopathy- associated eclampsia caused by retinal arteriolar narrowing due to systemic hypertension and ischemia. Previous studies have demonstrated subretinal/intraretinal fluid with or without serous retinal detachment in preeclampsia. Following our case, we report subretinal fluid, intraretinal fluid in the outer plexiform layer with retinal detachment and macular edema. The subretinal fluid and serous detachment were most likely caused by the changes in the fluid and ion-transport function of the retinal pigment epithelium (RPE). Conclusion : OCT can provide valuable information for diagnosis and follow-up retinopathy in preeclampsia/eclampsia.